Effect of delayed storage and continuous ethylene exposure on flesh reddening of 'Royal Diamond' plums - Vicente, Ariel Roberto; Crisosto, Carlos H.; Manganaris, George A. (My University, 2008)
BACKGROUND: Flesh reddening has been described as one of the manifestations of plum fruits to low-temperature storage for prolonged periods. The influence of factors such as ethylene and delayed storage has not been studied to date. In order to assess that, plum cv. 'Royal Diamond' fruits were (a) stored at 5°C (control), (b) held at 20°C for 2 days before storage at 5°C (delayed storage) or (c) maintained at 5°C under 15 μL L-1 ethylene. Fruits were then transferred to 20°C and ethylene, respiration, weight loss, firmness, soluble solids content, acidity, flesh reddening, anthocyanin accumulation and phenylalanine ammonia-lyase (PAL) activity were determined. RESULTS: Delayed storage fruits showed more extensive flesh reddening than control fruits, with increased PAL activity and higher anthocyanin accumulation. Symptoms were expressed more markedly when fruits were stored at 5°C in ethylene. CONCLUSION: Results indicated that the fruit ripening stage is a critical factor determining the susceptibility of 'Royal Diamond' plums to flesh reddening. Fruits continuously exposed to ethylene showed a dramatic increase in reddening, suggesting that ethylene contributes to the development of the disorder
Keywords: Chilling injury; Market life; Physiological disorder; Prunus salicina; Ripening stage